Effect of combined alcohol and tobacco exposure on risk of cancer of the hypopharynx. Issue 4 (December 1985) - Olsen, J; Sabroe, S; Ipsen, J
Abstract : The effect of moderate to heavy exposure to alcohol and tobacco on the risk of cancer of the hypopharynx is estimated in a case-control study. All incident hypopharyngeal cancer patients in Denmark who were under 75 years of age were compared with incident cases of laryngeal cancer and population sampled controls. The ascertainment of cases and controls took place during March 1980 to March 1982. Thirty-two patients with cancer of the hypopharynx, 321 patients with cancer of the larynx, and 1141 population sampled controls participated in the study. The effect of combined exposure to alcohol and tobacco seemed to be multiplicative rather than additive, a finding which is similar to that in laryngeal cancer patients. However, as there were only small numbers, only major deviations from the additive or multiplicative model for interaction would be detectable.